Suetonius and the problem of the succession in the Roman Principate in ‘The Lives of the Twelve Caesars’ - Luiz Leme, André (Romanitas - Revista de Estudos Grecolatinos, 2023)
By critically exploring some issues observed in the collection of biographies wrote by Gaius Suetonius Tranquillus (69-after 121/22 AD), called The Lives of the Twelve Caesars, we focus on those elements regarding the biographer’s political thought. We aim at investigating Suetonius’s views about the problem of the succession of imperial power in the Roman Principate at the 1st century AD, taking into consideration how the author evaluates the lives and actions of the principes of that period. Therefore, we will try to link his thoughts over that subject with the political trends related to his own time, that is, the early 2nd century AD, a period marked by the transfer of power from Trajan (53-117 AD) to Hadrian (76-138 AD).
Keywords: Suetonius; The Lives of the Twelve Caesars; Roman Principate; Hadrian